PENGEMBANGAN BAHAN AJAR STATISTIKA TERINTEGRASI MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR MAHASISWA PGSD UNIVERSITAS QUALITY - Dedi Holden Simbolon; Frikson Joni Purba (LP2MTBM MAKARIOZ, 2018)
This Research and Development (R & D) aims to produce more innovative statistics teaching materials by integrating them into guided, valid, practical and effective guided learning models in accordance with the National Standards of Higher Education. In addition to improving the quality of student learning outcomes in the course of statistics at the Universitas Quality. Furthermore, to know the effectiveness of teaching materials statistics development results that have been applied at the University of Quality. The study population is all students of PGSD Universitas Quality academic year 2017/2018. Sampling technique by using Purposive Sampling, which is student of semester V that take course of statistics. This research method uses Research and Development (R & D) method that adapted and modified by Borg & Gall. The work steps in the study include: (1) preliminary study, 2) development of teaching materials, 3) implementation of instructional use, 4) product effectiveness test. Instrument used in this research is achievement test of learning result. Furthermore, to test the hypothesis used t-test. From the result of t test for student learning result obtained thit = 3.246 compared on ttab 2.015 (5% significance level), so it can be said that thit > ttab or 3,246> 2,015. Through these results it can be concluded that the use of teaching materials statistics can give effect to student learning outcomes. Through these results it can be concluded that instruction-based instructional materials guided inquiry effectively improve student learning outcomes PGSD at Universitas Quality.